Carbohydrate-substituted N-heterocyclic carbenes Palladium complexes: High efficiency catalysts for aqueous Suzuki–Miyaura reaction. (February 2022) - Xie, Qian; Li, Jing; Wen, Xiaoming; Huang, Yanxia; Hu, Yunchi; Huang, Qing; Xu, Guohai; Xie, Yongrong; Zhou, Zhonggao
Abstract: Metal complexes that contain carbohydrate-substituent (Carb-) N-heterocyclic carbenes (NHCs) ligand have demonstrated great success as catalysts for organic synthesis reactions. In this study, four new Carb-NHC-Pd complexes 2a-d were prepared and their catalytic activities for Suzuki–Miyaura reaction were evaluated. The Carb-NHC-Pd complex behaved as a general surfactant which leads to the formation of a temporary oil-in-water contact interface, thereby promoting the Suzuki–Miyaura reaction. A long hydrophobic alkyl chain (– n C16 H33 ) was remotely linked to complex 2d, in which Carb-NHCs showed high electron-donating properties, and steric bulk with 1 JCH constant of 1 H NMR. Complex 2d exhibited a higher catalytic activity as compared with 2a (– n C2 H5 ), 2b (– n C4 H9 ), and 2c (– n C8 H17 ). A series of fluorene-cored materials with different aryl groups were synthesized with high yields (34 examples, 91–99%) under the optimized reaction conditions. Graphical abstract: Four new Carb-NHCs-Pd complexes 2a-d were prepared and their catalytic activities for aqueous Suzuki–Miyaura reaction were evaluated. One set of 1 H and 13 C NMR spectral signals were appeared during the preparation process of these complexes, implied pure β -anomer was formation. A long hydrophobic alkyl chain (– n C16 H33 ) was remotely linked to complex 2d, in which Carb-NHCs showed high electron-donating properties, steric bulk with 1 JCH constant of 1 H NMR and exhibited a highest catalytic activity. Dozens of organic small molecule fluorene-cored materials with different aryl groups were synthesized in excellent yields. Image 1 Highlights: Carb-NHCs-Pd complexes were prepared in pure β -anomer with a simple one-pot method. The catalytic activities of Carb-NHCs-Pd complexes were evaluated with aqueous Suzuki–Miyaura reactions. Carb-NHCs-Pd complex with a long hydrophobic alkyl chain (– n C16 H33 ) exhibited the highest catalytic activity. 34 examples of fluorine-cored OFMs were synthesized.